SOCIAL AWARENESS AND CREATIVITY ENHANCEMENT PROGRAM THROUGH E-LEARNING PLATFORM: A CASE OF MAIZBHANDER FOUNDATION’S MEDDHABIKASH PROGRAM, FATIKCHARI, BANGLADESH - Hoque, Syed Irfanul; Asgor, Muhammad Ali; Islam, Md Ariful (American Economic & Social Review, 2021)
Due to the pandemic situation, the whole world is in turmoil. The educational activities are being conducted via an e-Platform in Bangladesh. Social awareness and creativity enhancement Programs have also been limited from the wide range of conventional mode to virtual mode. In the meantime, many Social organizations and educational institutions have failed to manage their regular activities due to lack of technological support. Therefore, the purpose of this study is to examine the success of social awareness and creativity enhancement programs through the e-Learning platform. In order to measure the success of the program a quasi-experimental research design has been applied. In order to collect data, a well-structured creativity, and awareness scale has been adapted. A questionnaire has been administered twice with the same sample. Once before the program offered and again after their participation in the program. The test-retest reliability of the scale would also check with a minimum of α=.80. Therefore, the findings of the research will show how much the effectiveness of those activities increased. This study will assist the social workers, teachers, students and concerned authority in operating creativity enhancement related co-curricular and non-credited program through self-regulated distance learning in a developing country.